The Influence of Stress on Work Performance Through Leader Support Moderation in Digital Msmes in Denpasar City - Rettobjaan, Vitalia Fina Carla; Richadinata, Kadek Riyan Putra; Aristayudha, A.A. Ngr Bagus; Widnyani, Ni Made; Ada, Kadek Bramdhika; Dewi, Putu Febri Candra (Global Health Science Group, 2025)
The growth of the Micro, Small, and Medium Enterprises (MSMEs) sector in Denpasar City, Bali, is increasingly rapid along with the penetration of digital technology. Digital MSMEs are the main drivers of economic growth and job creation. However, amidst this progress, worker welfare and the performance of digital MSMEs still face challenges, especially work stress that can affect employee performance. Factors such as a competitive business environment and pressure to adapt to new technologies often increase stress among workers. This study aims to investigate the effect of stress on the work performance of digital MSME employees in Denpasar City, considering the moderating role of leader support. This study uses an observational analytical method with a quantitative approach and a cross-sectional design. Data were collected through structured questionnaires distributed to digital MSME employees in the Denpasar City area. The research sample consisted of 100 employees selected using the proportional random sampling technique. Data analysis was performed using statistical methods, including descriptive analysis to summarize respondent characteristics, correlation analysis to examine relationships between variables, and multiple regression analysis to test the effect of work stress on work performance. Additionally, a moderation analysis was conducted to assess the role of leader support in moderating the impact of work stress on performance. The validity and reliability of the questionnaire were tested using Cronbach’s Alpha and factor analysis to ensure consistency and accuracy of the measurement instruments. Hypothesis testing was carried out at a 95% confidence level (α = 0.05) to determine the significance of the relationships among variables.The results showed that work stress had a negative effect on work performance, while leader support had a positive effect on work performance. Leader support was also shown to moderate the relationship between work stress and work performance. These findings provide important insights for digital MSME owners to understand the role of leader support in creating a healthy and productive work environment. This study is expected to provide practical recommendations for MSME managers to manage stress and improve employee well-being and business performance.